Low to high-frequency noise behavior investigation of steeper sub-threshold swing NC-GeFinFET. (January 2023) - Maurya, Ravindra Kumar; Saha, Rajesh; Bhowmick, Brinda
Abstract: The role of noise effect, in presence of Gaussian-trap distribution on the negative capacitance germanium FinFET (NC-GeFinFET) by using Sentaurus-TCAD is investigated. Incorporation of ferroelectric FE-layer in NC-GeFinFET, I O N boosts by almost 18% compared to the baseline FinFET. Also steeper sub-threshold swing (SS) of 7.4 mV/decade is achieved by using the FE-layer of thickness ( t f e ) 6 nm at the room temperature. Result reports how the 1 f noise and Generation-Recombination (G-R) noise plays an important role in net drain current spectral density (net S i d ) for the proposed device up to mid frequency range, and the diffusion noise dominates in the high frequency range. This study highlights the analysis of net S i d with respect to frequency for different t f e . The minimum net S i d value 4.45 × 10 − 16 A 2 /Hz is achieved at 10 Hz, in presence of Gaussian-trap, for t f e 6 nm and is compared with the results for t f e 4 nm and 5 nm. This shows the importance of FE-layer in achieving low net S i d, especially in high frequency regime.